The influence of college students' exercise participation on feelings of self-deficiency: the mediating effect of social support - Xia, Yunping; Luo, Min; Liu, Bo; Fan, Yunxiang; Tang, Kai; Tang, Yong; Zhang, Xiang (Frontiers in Psychology, 2025)
ObjectiveTo explore the influence of college students' exercise participation on their feelings of self-deficiency and its mechanisms, with social support as a mediating variable.MethodsThe study utilized the Physical Activity Rating Scale (PARS-3), the Feelings of Inadequacy Scale (FIS), and the Social Support Rating Scale (SSRS). A stratified random sampling method was used to select 981 college students from different provinces and universities for a questionnaire survey. Statistical methods, including confirmatory factor analysis, regression analysis, and the Bootstrap method, were employed for data analysis.ResultsExercise participation significantly and negatively predicted college students' feelings of self-deficiency. Social support exhibited a significant mediating effect between exercise participation and self-deficiency. Furthermore, the three dimensions of social support—subjective support, objective support, and support utilization—showed significant indirect effects. The mediation pathways were as follows: exercise participation → subjective support → self-deficiency, exercise participation → objective support → self-deficiency, and exercise participation → support utilization → self-deficiency.ConclusionExercise participation significantly reduces feelings of self-deficiency among college students, either directly or indirectly through social support. In the future, universities can help mitigate students' self-deficiency and promote their physical and mental wellbeing by optimizing physical activity spaces and constructing social support networks from the perspectives of exercise participation and social support.